The Effect of Promotion and Brand Image on Consumer Buying Interest in Ayuithafreshmarket - Hayyu Rahmawati; Sri Ernawati; Ismunandar Ismunandar (Universitas Indonesia Membangun (Inaba), 2026)
This study aims to examine the effects of promotion and brand image on consumers’ purchase intention at AyuithaFreshMarket. Increasing competition among retail and fresh-goods stores requires AyuithaFreshMarket to implement appropriate strategies to keep consumers interested in buying. Promotion functions as a communication tool to convey product information, while brand image shapes consumers’ perceptions and trust in the store. The research used a quantitative method with a causal-associative approach. Data were collected via questionnaires distributed to 77 consumer respondents of AyuithaFreshMarket, using purposive sampling. Data analysis included validity and reliability tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination using SPSS. The results show that promotion and brand image, both partially and simultaneously, have a positive and significant effect on consumers’ purchase intention at AyuithaFreshMarket. The brand image variable has the most dominant influence compared with promotion, indicating that consumers’ positive perceptions of the AyuithaFreshMarket brand are a key factor driving purchase decisions. It is recommended that AyuithaFreshMarket continue to increase the intensity of informative and attractive promotions and strengthen its brand image through consistent product quality and service so that consumers’ purchase intention continues to rise.